IDENTIFIKASI JENIS LEBAH Trigona spp. PADA ZONA PEMANFAATAN HUTAN DESA MENUA SADAP KECAMATAN EMBALOH HULU KABUPATEN KAPUAS HULU - veronika kerisna; Farah Diba; Reine Suci Wulandari (Universitas Tanjungpura, 2019)
Bee is a social insect and some of bee produced honey which used as food source for humankind. Based on biology characteristic, there are two kinds of bee, stingy bee and stingless bee. Stingy bee is Apis sp and Trigon sp is stingless bee. The aim of research is to identified the stingless bee from Trigon sp on forest village in Menua Sadap Village, Embaloh Hulu District, Kapuas Hulu Regency. Menua Sadap forest village area was 1.382 hectare and divided into four zone, namely production zone, conservation zone, tourism zone and utilization zone.The research was conducted on utilization zone of forest village for one month in the forest. The method of research used survey with purposive sampling. The data collected consist of find the Trigona sp bee in the tree and their nest, collected the bee and identified the bee.Result of the research found eight types of Trigona sp in utilization zone of Menua Sadap forest village. The name of Trigona bee were Heterotrigona itama Cockerell, Lepidotrigona terminate Smith, Tetragonula sirindhornae Michener & Boongird, Tetragonula fuscobaltaeta Cameron , Tetrigona binghami Schwarz, Tetragonula laeviceps Smith, Tetragonula collina Smith and Geniotrigona lacteifasciata Cameron. The vegetation on forest village as a nest of the bee consist of Shorea spp, Koompasiana excelsa, and Ficus sp. The community in Menua Sadap village has harvested the honey from Trigona sp, but only from three types of bee, namely Heterotrigona itamaCockerel, Tetragonula collinaSmithand Geniotrigona lacteifasciataCameron. Menua Sadap forest village was a potential site for stingless bee and a potential source for harvesting honey.